Pengelolaan Sampah Rumah Tangga Berbasis Pemberdayaan Masyarakat Melalui Program PILAH - Yasinta Indah Widyaningsih; Zulkifli Walangadi; Rezki Ramdani; Azharatul Jannah; Salwah Suardi (Paramacitra Jurnal Pengabdian Masyarakat, 2026)
Waste management remains a major environmental challenge in Bonto Perak Village, Pangkajene and Islands Regency. Low community awareness and unequal collection services contribute to environmental pollution. This community engagement program aimed to enhance residents’ knowledge and skills in waste segregation and composting through the PILAH (Integrative Waste Management Guide) program. The method included problem identification, root cause analysis, goal setting, activity design, field implementation, and monitoring and evaluation. Data were collected through field observations and interviews with 262 residents for baseline identification, as well as pre-test and post-test assessments of 17 key participants to measure behavioral changes. Results showed significant improvements in the intervention group, with average scores increasing for knowledge (5.35 to 6.41), attitude (22.29 to 22.47), and action planning (10.64 to 11.17). Participants demonstrated higher motivation for composting and reducing waste burning. The PILAH program proved effective in improving sustainable waste management behaviors and has high replication potential with local adaptations.